2017
DOI: 10.1177/0363546516677794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surgical Factors on Cartilage Can Be Detected Using Quantitative Magnetic Resonance Imaging After Anterior Cruciate Ligament Reconstruction

Abstract: Prolonged relaxation times in multiple regions demonstrate how the injury affects the entire joint after an ACL tear. Changes observed in the uninjured knee may be caused by increased loading during rehabilitation, especially in the patellofemoral articular cartilage and distal femur. Relaxation times in the tibial regions may be predictive of patient symptoms at 6 months. These same regions are affected by surgical timing as early as 30 days after injury, but this may partially be reflective of the severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…A previous comparison of quantitative cartilage MRI metrics and PROs following ACL reconstruction found that side-to-side differences in cartilage T1rho values measured prior to surgery were predictive of all KOOS outcomes except for sports function at 1 year following surgery 48 . In a larger study, prolonged T1rho and T2 values were associated with worse KOOS Symptoms, Pain and Activities of Daily Living measured 6 months post-surgery 49 . The observed small but significant correlation between decreased UTE-T2* profile slope and worse KOOS Symptoms at just 2 years after ACLR in the current study similarly shows a potential relationship between cartilage structural changes and clinical outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…A previous comparison of quantitative cartilage MRI metrics and PROs following ACL reconstruction found that side-to-side differences in cartilage T1rho values measured prior to surgery were predictive of all KOOS outcomes except for sports function at 1 year following surgery 48 . In a larger study, prolonged T1rho and T2 values were associated with worse KOOS Symptoms, Pain and Activities of Daily Living measured 6 months post-surgery 49 . The observed small but significant correlation between decreased UTE-T2* profile slope and worse KOOS Symptoms at just 2 years after ACLR in the current study similarly shows a potential relationship between cartilage structural changes and clinical outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…Composite metric sequences including T 1ρ and T 2 have been associated with the PROM KOOS, pain after ACL reconstruction and with synovial fluid biomarkers at the time of surgery30, 31, 32. Change in these compositional measures may reflect differences in surgical factors after ACL reconstruction and the pre-injury joint structure 33 .…”
Section: Resultsmentioning
confidence: 99%
“…These regional alterations in loading may affect cartilage health (proteoglycan content and collagen organization) and may be more accurately assessed by quantitative magnetic resonance imaging including T1rho and T2 scanning protocols. 3,53 Such modalities provide more detailed and earlier information on cartilage health than commonly used radiographic measures and may be useful to determine whether ACLR augmented with LET accelerates cartilage degeneration. 38 Differences between our study and previously published work include surgical technique, applied loads, and the conditions of the knee that were compared.…”
Section: Discussionmentioning
confidence: 99%